Expatriation stressors and the well-being of accompanying partners: a commonality analysis approach - Katja Herrmann Aegerter; Andrea H. Meyer; Jens Gaab; Yoon Phaik Ooi; Yoon Phaik Ooi (Frontiers in Psychology)
IntroductionThis cross-sectional study aims to explore the unique and shared effects of non-work expatriation stressors on the well-being of expatriate partners and spouses who relocate on a regular basis.MethodsA cohort of 207 internationally mobile adults was recruited through international associations, foreign ministries, social media, and personal networks. Participants completed a quantitative online questionnaire that assessed various psychological factors. We employed commonality analysis to evaluate the unique and joint impact of perceived stress, perceived social support, isolation, and perceived cultural distance on partner well-being, using validated psychological scales.ResultsPerceived stress proved to be the most impactful unique contributor to partner well-being, while isolation emerged as the second strongest unique predictor. Perceived social support showed the most substantial combined effect with stress and isolation. The variance explained by perceived cultural distance was marginal, suggesting that stress and isolation are more influential factors in this population. The control variables (age, gender, duration of residence in the host country, and frequency of relocation) showed no significant contribution in combination with the stressors.DiscussionBuilding on the findings of existing research, these results provide further support for the need for tailored interventions to promote the well-being of expatriate partners. Practical implications include involving partners in pre-assignment screening processes, investing in structured social support systems to reduce isolation, and developing comprehensive, culturally sensitive policies that address the range of challenges faced by expatriate partners.